Hormonal contraceptive use related to breast cancer among women in Indonesia: a nationwide study - Solikhah Solikhah; Monthida Sangruangake; Ratu Matahari; Wulan Rahmadhani; Rochana Ruliyandari (Intelektual Pustaka Media Utama, 2022)
Breast cancer remains a global problem, including Indonesia. However, research findings regarding the influence of hormonal contraceptive use on breast cancer have not been conclusive. Therefore, this study aimed to investigate whether there was any association between hormonal contraception use and breast cancer among women in Indonesia. We assessed 3,517 participants who participated in this study conducted through the Indonesian Family Life Survey wave five during 2014-2015. A logistic regression model was performed to analyse data. The precentage of breast cancer cases in this study was 0.34%, with a total of 1,574 respondents (44.75%) having used hormonal contraceptive for more than five years. After controlling for confounders, the hormonal contraceptive use had significantly lower to have breast cancer incidence (ORadj=0.10; 95% CI=0.03-0.40; p<0.05) compared to women using non-hormonal contraceptive, while the long-term hormonal contraception use (more than five years) did not affect breast cancer incidence. Hormonal contraceptive use was associated with breast cancer; however, the evidence from our findings indicated that the magnitude of the risk was small.